The Pedagogy of Translation: Learning from Innu activist Elizabeth Penashue’s Diaries - Yeoman, Elizabeth (Journal of the Canadian Association for Curriculum Studies, 2012)
A collaborative project to translate and edit Innu cultural and environmental activist Elizabeth Penashue’s diaries in Innu-aimun for publication raises aesthetic questions about choice of images, wording, interpretation, and contextualization. This article considers the possibilities of translation as solidarity and as pedagogy, and the potential contribution of the translated diaries to world literature and to an education in the humanities.